A new ductile fracture criterion considering both shear and tension mechanisms on void coalescence. (March 2021) - Li, Xifeng; Yang, Wenbing; Xu, Dongkai; Ju, Ke; Chen, Jun
A new ductile fracture criterion is proposed based on three stages of ductile fracture: void nucleation, growth and coalescence from the microscopic viewpoint. Based on the observation of SEM fracture surfaces of AA2024-T351 aluminum alloy sheet and bar samples under different stress states, it is assumed that the void aggregation is controlled by shear or shear-tension fracture mechanism according to the stress state. And the stress triaxiality is deemed as the only influence factor for controlling the void growth. The new ductile fracture criterion applied to a wide range of stress triaxiality is built. By fitting the available testing data of AA2024-T351 aluminum alloy and AISI 1045 steel, the fracture loci in the stress triaxiality, Lode parameter and equivalent fracture strain space (η, L, ε ¯ f ) built by the new criterion are compared with those by DF2014, Hu criterion, modified Mohr-Coulomb criterion (MMC) and Hosford- Coulomb (H-C) criterion. The fitting results prove better prediction accuracy for the new criterion. To further compare the stability of these criteria, the fracture loci in the space of (η, L, ε ¯ f ) for AA2024-T351 alloy are established by only fitting five tests. The new criterion can still well predict the equivalent fracture strain (ε ¯ f ). Compared with DF2014, Hu criterion, MMC and H-C criterion, the average errors of the new criterion are reduced by 26.72%, 20.07%, 31.78% and 34.62%, respectively. Furthermore, the maximum errors are reduced by 49.62%, 27.31%, 33.76% and 29.91%, separately. Therefore, the new fracture criterion has higher prediction accuracy and better prediction stability. Last but certainly not least, the new criterion can predict more accurately under high stress triaxiality conditions.